The contribution of δ subunit-containing GABAA receptors to phasic and tonic conductance changes in cerebellum, thalamus and neocortex - Brickley, Stephen G.; Ye, Zhiwen; McGee, Thomas P.; Houston, Catriona M. (Frontiers in Neural Circuits, 2013)
We have made use of the delta subunit-selective allosteric modulator DS2 (4-chloro-N-[2-(2-thienyl)imidazo[1,2-a]pyridine-3-yl benzamide) to assay the contribution of delta-GABAARs to tonic and phasic conductance changes in the cerebellum, thalamus and neocortex. In cerebellar granule cells, an enhancement of the tonic conductance was observed for DS2 and the orthosteric agonist THIP (4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol). As expected, DS2 did not alter the properties of GABAA receptor-mediated inhibitory postsynaptic synaptic currents (IPSCs) supporting a purely extrasynaptic role for delta-GABAARs in cerebellar granule cells. DS2 also enhanced the tonic conductance recorded from thalamic relay neurons of the visual thalamus with no alteration in IPSC properties. However, in addition to enhancing the tonic conductance DS2 also slowed the decay of IPSCs recorded from layer II/III neocortical neurons. A slowing of the IPSC decay also occurred in the presence of the voltage-gated sodium channel blocker TTX. Moreover, under conditions of reduced GABA release the ability of DS2 to enhance the tonic conductance was attenuated. These results indicate that delta-GABAARs can be activated following vesicular GABA release onto neocortical neurons and that the actions of DS2 on the tonic conductance may be influenced by the ambient GABA levels present in particular brain regions.